Identification of progressive pulmonary fibrosis: consensus findings from a modified Delphi study - Athol U. Wells; Simon L. F. Walsh; Ayodeji Adegunsoye; Vincent Cottin; Sonye K. Danoff; Anand Devaraj; Kevin R. Flaherty; Peter M. George; Kerri A. Johannson; Martin Kolb; Yasuhiro Kondoh; Andrew G. Nicholson; et al. (Respiratory Research)
Abstract Background We sought consensus among practising respiratory physicians on the prediction, identification and monitoring of progression in patients with fibrosing interstitial lung disease (ILD) using a modified Delphi process. Methods Following a literature review, statements on the prediction, identification and monitoring of progression of ILD were developed by a panel of physicians with specialist expertise. Practising respiratory physicians were sent a survey asking them to indicate their level of agreement with these statements on a binary scale or 7-point Likert scale (− 3 to 3), or to select answers from a list. Consensus was considered to be achieved if ≥ 70% of respondents selected the same answer, or, for responses on a Likert scale, the median score was ≤ –2 (disagree/not important) or ≥ 2 (agree/important) with an interquartile range ≤ 1. There were three rounds of the survey. Results Surveys 1, 2 and 3 were completed by 207, 131 and 94 physicians, respectively, between March 2022 and July 2023. Decline in forced vital capacity (FVC), decline in diffusing capacity of the lungs for carbon monoxide, and increased fibrosis on high-resolution computed tomography (HRCT) were ranked as the most important endpoints for determining progression. Consensus was reached that progression on HRCT or a decline in FVC ≥ 10% from baseline is sufficient to determine progression, and that small declines in multiple endpoints indicates progression. Consensus was reached that a histological pattern of usual interstitial pneumonia (UIP) is a risk factor for progression of ILD, but that a biopsy to look for a UIP pattern should not be performed solely for prognostic reasons. Consensus was not reached on the time period over which progression should be defined. There was consensus that appropriate management of ILD depends on the type of ILD, and that ‘despite adequate management’ or ‘despite usual management’ should be included in the definition of progression. Conclusions This modified Delphi process provided consensus statements on the identification of ILD progression that were supported by a broad group of clinicians and may help to inform clinical practice until robust evidence-based guidelines are available.